PENYULUHAN FISIOTERAPI MENGENAI KASUS LOW BACK PAIN PADA LANSIA DI KEC. SIDAMANIK KAB. SIMALUNGUN - I Ngurah Gede Verar Fujastawan; Isa Harpika Br. Ginting; Jesicca Hasibuan (Yayasan Nusantara Hasana Berdikari, 2022)
This community service report aims to improve elderly understanding regarding the causes, prevention, and management of low back pain through physiotherapy counseling in Sidamanik District, Simalungun Regency. The counseling activities were implemented using educational materials such as posters, leaflets, and live demonstrations conducted by experienced physiotherapists. Evaluations were carried out using pretest and posttest methods among 22 elderly participants aged between 60 and 68 years. The results revealed an improvement in understanding from 23% in the pretest to 100% in the posttest, indicating the success of the counseling method in raising awareness about the importance of proper posture and healthy activities to prevent low back pain. This report provides detailed descriptions of the activities, evaluation methods, result analyses, and recommendations for further development of similar community service programs in the future